Receptors and Signaling Pathways for Recognition of Bacteria in Livestock and Crops: Prospects for Beneficial Microbes in Healthy Growth Strategies - Villena, Julio; Kitazawa, Haruki; Van Wees, Saskia C. M.; Pieterse, Corné M. J.; Takahashi, Hideki (Frontiers in Immunology, 2018)
Modern animal and crop production practices are associated with the regular use of antimicrobials, potentially increasing selection pressure on bacteria to become resistant. Alternative approaches are needed in order to satisfy the demands of the growing human population without the indiscriminate use of antimicrobials. Researchers have brought a different perspective to solve this problem and have emphasized the exploitation of animal- and plant-associated microorganisms that are beneficial to their hosts through the modulation of the innate immune system. There is increasing evidence that plants and animals employ microbial perception and defense pathways that closely resemble each other. Formation of pattern recognition receptor (PRR) complexes involving leucine-rich repeat (LRR)-containing proteins, mitogen-activated protein kinase (MAPK)-mediated activation of immune response genes, and subsequent production of antimicrobial products and reactive oxygen species (ROS) and nitric oxide (NO) to improve defenses against pathogens, add to the list of similarities between both systems. Recent pioneering work has identified that animal and plant cells use similar receptors for sensing beneficial commensal microbes that are important for the maintenance of the host's health. Here, we reviewed the current knowledge about the molecular mechanisms involved in the recognition of pathogenic and commensal microbes by the innate immune systems of animal and plants highlighting their differences and similarities. In addition, we discuss the idea of using beneficial microbes to modulate animal and plant immune systems in order to improve the resistance to infections and reduce the use of antimicrobial compounds.